Tindakan Amerika Serikat Dalam Menarik Diri Dari Paris Agreement Dalam Kerangka Hukum Internasional - Mush'ab Al Ma'ruf; Mahendra Putra Kurnia; Syukri Hidayatullah (Fakultas Hukum Universitas Mulawarman, 2020)
This research is motivated by the United States, which withdrew from the Paris Agreement because for the United States, the Paris Agreement is an agreement that weakens the economy. Following Article 28 of the Paris Agreement, this action raises problems that the United States cannot withdraw before 2020. In this case, there needs to be legal clarity in binding the country to global climate protection. The act of withdrawing the United States from the Paris Agreement would undoubtedly be a problem for the countries incorporated in it. In this case, the Paris Agreement continues to run as it should because the United States withdrew using the mechanisms contained in the Paris Agreement. Still, the United States continues to handle climate change because it does not come out of the Convention (UNFCCC). Then in the campaign and carbon trading, the United States should compensate for having left obligations as a developed country party following the Paris Agreement.